Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1002/app.1995.070580412
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and experimental study of gas penetration in a gas‐assisted injection‐molded spiral tube

Abstract: Characteristics of gas penetration and polymer melt flow in gas‐assisted injection molded spiral tubes was investigated by simulations and experiments. Distribution of the skin melt thickness along the gas flow direction was measured, and gas penetration in the primary and secondary stages was identified. An algorithm based on the control‐volume/tiniteelement method combined with a particle‐tracing scheme using a dual‐filling‐parameter technique is utilized to predict the advancements of both melt front and ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 1 publication
0
20
0
Order By: Relevance
“…So far, most literatures mainly focused on the mathematic simulation of gas penetration, [4][5][6][7][8][11][12][13][14][15] the effect of the gas channel design on the gas penetration behavior, 3,4,6,16 molding window, 3,10,17 the influence of gas channel shape on the mechanical properties [18][19][20] and so on, while studies on the morphology development in GAIM part and the relationship between microstructure and macroproperties are limited. Chien 21 explored the influence of gas channel shape on the mechanical properties of GAIM moldings as well as the crystallnity of polyamide (PA), and found that maximum tensile load and ultimate tensile stress of PA moldings exhibited significant dependence on part thickness because of higher degree of crystallinity.…”
Section: Introductionmentioning
confidence: 99%
“…So far, most literatures mainly focused on the mathematic simulation of gas penetration, [4][5][6][7][8][11][12][13][14][15] the effect of the gas channel design on the gas penetration behavior, 3,4,6,16 molding window, 3,10,17 the influence of gas channel shape on the mechanical properties [18][19][20] and so on, while studies on the morphology development in GAIM part and the relationship between microstructure and macroproperties are limited. Chien 21 explored the influence of gas channel shape on the mechanical properties of GAIM moldings as well as the crystallnity of polyamide (PA), and found that maximum tensile load and ultimate tensile stress of PA moldings exhibited significant dependence on part thickness because of higher degree of crystallinity.…”
Section: Introductionmentioning
confidence: 99%
“…A high injection velocity will induce a higher shear rate and lead to a higher level of gross. However, the influence in the gas 6 Effect of mould temperature on glossy difference and chromatic aberration of PP GAIM parts with five different gas channel designs 7 Effect of melt temperature on glossy difference and chromatic aberration of PP GAIM parts with five different gas channel designs 8 a X-ray diffraction pattern for gas channel and plate under mould temperature 40uC; b X-ray diffraction pattern for gas channel and plate under mould temperature 60uC channel is less significant because of its large dimensions and the associated shear rate and the degree of crystallinity is lower. Consequently, when the injection velocity is increased, the gloss increase in the gas channel and flat plate is different leading to larger gross differences (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Cornell University, in collaboration with the AC Company of the USA, used the C-Mold software to investigate the structural analysis of GAIM products [1]. Chen et al [2] studied the one dimension flow characteristics of the mold to measure the extension of the hollow rate of products depending on the mold and on melt temperatures. Soh and Chung [3] used the pressure gradient with the steady-state flow equation to predict the direction of gas penetration.…”
Section: Introductionmentioning
confidence: 99%